Imaging Characteristics of Neovascular and Atrophic Pachychoroidal Spectrum Diseases - Hua, Rui; Zhang, Meixia (Frontiers in Medicine, 2022)
Background: This study qualitatively and quantitatively compared imaging characteristics between neovascular and atrophic pachychoroid spectrum disease (PSD) by optical coherence tomography (OCT), and OCT angiography (OCTA). Methods: The subtypes of PSD were identified by multi-modality imaging approaches. Subfoveal choroidal thickness (SFCT), choroidal vascular index (CVI), and vascular density of choroidal neovascularization (CNV) were measured. Results: The CVI and SFCT of 174 PSD eyes were 67.6%±5.48% and 362.2±131.88 μm, respectively. After adjustment for age, linear regression indicated that SFCT was positively associated with CVI (p<0.001), and patched hyper-reflective lesions in choriocapillaris layers (p=0.009). Compared with neovascular PSD eyes, atrophic PSD eyes had similar patient age (57.1±16.72 years, p=0.639), SFCT (332.0±111.00 μm, p=0.51), and CVI (67.6%±3.94%, p=0.527). There were no differences between polypoidal choroidal vasculopathy (PCV) eyes with aneurysmal polypoidal lesions and PCV eyes with tangled polypoidal lesions in terms of age, CVI, SFCT, vascular density, or the occurrence of double layer signs (DLSs, all p>0.05). Logistic regression indicated that age (p=0.003), SFCT (p=0.003), patched hyper-reflective lesions in choriocapillaris layers (p=0.009), and DLSs (p<0.001) were predictive factors for CNV progression in PSD eyes (all p<0.05). Conclusions: Our study highlighted the similarities in SFCT and CVI between neovascular and atrophic PSD, all of which were late stage lesions. Besides, age, SFCT, patched hyper-reflective lesions in choriocapillaris layers, and DLSs were risk factors for CNV in PSD. Our results showed that atrophic PSD is an important change in the late stage of PSD disease, which is helpful for in-depth understanding of the pathological mechanism of PSD and corresponding intervention.